Applications of guar gum and its derivatives in petroleum industry: A review - Abdulraheim M.A. Hasan; Manar E. Abdel-Raouf (Egyptian Journal of Petroleum)
Green chemistry approach is growing rapidly and the replacement of petroleum derived materials with bio-based materials is greatly enhanced for environmental and health concerns. Polymers from renewable natural resources have attracted an increasing amount of attention over the last three decades, predominantly due to two main reasons: firstly environmental concerns, and secondly the realization that our petroleum resources are finite. Natural polymers are available in large quantities from different renewable sources, while synthetic polymers are produced from non-renewable petroleum resources. They include proteins and polysaccharides. Among the most important polysaccharides is Guar gum which has been extensively used in a wide range of applications due to its unique properties. The objective of this review is to focus the light on Guar Gum and its derivatives. The chemical structure, sources, chemical modification, physical properties (mechanical properties and thermal stability), and some potential industrial applications are reviewed and discussed. Keywords: Natural polymers, Guar gum, Chemical modification, Drilling fluids, Thickening agents